Assessment of the Operating Temperature of Crystalline PV Modules Based on Real Use Conditions - Giuseppina Ciulla; Valerio Lo Brano; Vincenzo Franzitta; Marco Trapanese (International Journal of Photoenergy)
Determining the operating temperature Tc of photovoltaic panels PV is important in evaluating the actual performance of these systems. In the literature, different correlations exist, in either explicit or implicit forms, which often do not account for the electrical behaviour of panels; in this way, estimating Tc is based only on the passive behaviour of the PV. In this paper, the authors propose a new implicit correlation that takes into account the standard weather variables and the electricity production regimes of a PV panel in terms of the proximity to the maximum power points. To validate its reliability, the new correlation was tested on two different PV panels (Sanyo and Kyocera panels) and the results were compared with values obtained from other common correlations already available in the literature. The data show that the quality of the new correlation drastically improves the estimation of the photovoltaic operating temperature.